ChemInform Abstract: An Efficient Synthesis of Novel Dibenzoxdiazepine‐Fused Heterocycles Through a Multicomponent Reaction. Issue 15 (April 2015) - Qian, Zhiwei; Yang, Anjiang; An, Weiteng; Yu, Ting; Wang, Xin; Zhang, Yongliang; Shen, Jingkang; Meng, Tao
Abstract: The atropisomeric properties observed in case of products obtained by the transformation of 2‐amino‐5‐haloheterocycles, 2‐isocyanophenyl acetate and aryl aldehydes equipped with electron‐withdrawing substituents is examined.